Recovery management in sport: Overview and outcomes of a nine-year multicenter research program - Wiewelhove, T.; Schneider, C.; Kellmann, M.; Pfeiffer, M.; Meyer, T.; Ferrauti, A. (International Journal of Sports Science & Coaching, 2024)
The nine-year multicenter research project, titled REGman—Optimization of Training and Competition: Management of Regeneration in Elite Sports—aimed to advance the understanding of recovery management in sports and generate practical recommendations. In this article, we outline the overarching research program that links the specific research strands and outputs during the two federal funding cycles (2012-2021) and summarize the main project findings. The two-stage conceptual framework involved investigating monitoring measures for short-term fatigue and recovery, as well as assessing the efficacy of various recovery interventions. These interventions encompassed psychological relaxation and recovery strategies, sleep, cooling techniques like precooling, percooling, cold water immersion, or whole-body cryotherapy, compression garments, active recovery, stretching, heating interventions such as sauna or contrast water therapy, massage, and foam rolling. The findings revealed inconclusive or marginal effects of recovery interventions at the group level, while indicating possible interindividual differences in responses. Additionally, the findings highlighted the effectiveness of diverse monitoring measures, showing satisfactory sensitivity in tracking performance changes related to fatigue and recovery. The use of individualized reference ranges significantly improved classification accuracy compared to group-based reference ranges. Athletes and coaches are encouraged to prioritize fundamental aspects of training and recovery: meticulous training planning and execution, effective sleep management, and proper nutrition. Furthermore, monitoring and analyzing individual responses, even though it demands suitable methodologies and presents challenges in high-performance sports environments, can yield valuable insights for personalized recovery management. If these aspects are comprehensively addressed, and resources allow, additional recovery strategies might be explored.